Influence of thermophoresis and thermal radiation on mass transfer and heat of Three Dimensional maxwell fluid in presence of Magnetic field (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
The study is about Maxwell , three dimensions of non – Newtonian fluid. Method of th Homotopy applied to analysis mass transfer and heat with thermophoresis effects